AN UPDATE ON PHARMACOLOGICAL PROFILE OF BOSWELLIA SERRATA - PILKHWAL, NAMEETA; DHANESHWAR, SUNEELA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Boswellia serrata (Burseraceae) is the most ancient and respected herbs in Ayurveda. In Unani system of medicine, oleo-gum resin of Boswellia serrata named Kundur played a prime ingredient role in modern quality perfumes. The gum is used as a remedy for treatment of illness especially skin diseases and rheumatism in Indian system of medicine (Sidha, Ayurvedic and Unani) for last diverse centuries. Salai guggul is one of the accepted drugs for various complaints such as dyspepsia, dysentery, lung diseases, urinary disorder, haemorrhoids and corneal ulcer in Unani system of medicine for the last several decades. The present article is aimed to provide an overview on various pharmacological activities of Boswellia serrata. The resin fraction of salai guggal is rich in boswellic acids and its essential oils that are composed of a mixture of mono, di and sesquiterpenes while gum fraction chiefly contains pentose and hexose sugars. The oleo-gum resin is quite popular among the practitioners of traditional system and possesses wide range of useful biological properties such as antiasthmatic, anticancer, antifungal, anticomplementary, antihyperlipidemic, antiinflammatory, antiarthritic, antirheumatic, antidiarrheal, antimicrobial, antifungal and analgesic. An exhaustive review of literature was performed using various databases on science direct, scopus, pubmed, google scholar and free patents online. This review is a sincere attempt to discuss and present the current status of pharmacological profile of Boswellia serrata.